Protective Effects of Dietary Flavonoids in Diabetic Induced Retinal Neurodegeneration - Ibrahim Al-Dosary, Dalia; S. Alhomida, Abdullah; S.Ola, Mohammad (Current Drug Targets, 2017)
Background: Diabetic retinopathy is one of the serious complications of diabetes and the leading cause of decreased vision and blindness worldwide. Neurodegeneration has been recognized as initiating factor in causing the retinal damage, which leads to micro-vascular damage in diabetic retinopathy. Diabetes-induced oxidative stress is believed to be the key factor that damages neurons in the diabetic retina. Various therapeutic approaches for effective attenuation of increased oxidative stress by antioxidants have emerged. One such approach is to utilize dietary flavonoids, which have been found to possess powerful antioxidant activity. Some of the naturally occurring flavones possess anti-diabetic effects by enhancing insulin sensitivity and reducing plasma glucose levels in diabetic animal models. Objective: Considering the importance of developing new antioxidant compounds and the relevance of their applications in the treatment of diabetes and its complications, in this review article, we discuss and highlight various neuroprotective mechanisms of flavonoids in the diabetic retina. Results: Dietary supplementation of flavonoids to diabetics may reduce oxidative stress, which in turn might ameliorate apoptosis and the levels of neurotrophic factors in the diabetic retina. Conclusion: This approach will elucidate a novel strategy for preventing and treating diabetic retinoneuropathy the leading cause of low vision and blindness.
Keywords: retina